Efficiency and Humanism: The Impact of the Humanistic Charting Tool on Patient Experience in the Emergency Department - Namrata Garg; Omid Boozarpour; Jose Alaras; Ivy Tran; Christopher R. Peabody; Nicholas Stark (Western Journal of Emergency Medicine, 2026)
Introduction: Emphasis on documentation challenges clinicians to strike a balance between efficiency and individualized care, often leading to the depersonalization of patient interactions. The Humanistic Charting Tool (HCT) addresses this by integrating the patient’s voice into the electronic medical record (EHR). The objective of this study was to examine whether use of the HCT during emergency department (ED) visits is feasible and improves key patient experience metrics. Methods: The study took place in an urban, academic hospital. Patients in the ED completed the HCT while waiting to see a clinician. The patient’s responses were condensed into a two-page summary and uploaded into their EHR. Clinicians were asked whether they used the HCT for each patient at the end of the encounter, and patients completed precare and postcare surveys assessing key experience metrics. Our primary outcome measure was changes in patient experience metrics, including key Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) metrics. Our secondary outcome measure was subgroup analyses among patients facing barriers to care. Results: Approximately 2.8% of the total ED patients were enrolled during the study period. Overall, 129 patients filled out the HCT, and 97 (74%) patients had complete survey data. A total of 65 clinicians participated in the study including 32 attending physicians, 23 resident physicians, and 10 advanced practice practitioners (APP). Clinicians used the HCT for 51 (53%) of these patients. Patients demonstrated significant improvements in feeling that clinicians listened carefully (79% to 92%; P < .001), took their preferences into account (61% to 74%; P = .01), treated them with courtesy and respect (85% to 94%; P < .001), and knew important information about them (43% to 52%; P = .01). Patients who did not have a regular clinician (n = 25 [26%]) had a significantly greater increase in feeling involved in their treatment discussion (36% to 60% vs 59% to 66%; P = .05). Patients who endorsed at least one social need (n = 15 [16%]) had a significantly greater increase in being listened to carefully (53% to 73% vs 84% to 95%; P = .01). No statistical significance was found between patients whose clinicians used the HCT versus not. Conclusion: The Humanisticc Charting Tool demonstrated feasibility and was associated with improvements in patient experience within the ED. This tool has the potential for patients to share their narratives and enrich their own healthcare experience, which is invaluable in a high-stakes, time-sensitive environment. The results also highlight a novel finding that the HCT may help mitigate disparities in communication, trust, and engagement that disproportionately affect vulnerable populations. This study supports the further development of humanism-centered tools within healthcare systems.